Komunikasi Interpersonal Barista Coffee Shop - Alya Nurulaeni; Aning Sofyan (Bandung Conference Series: Public Relations, 2023)
Abstract. Currently, the coffee shop business is one of the businesses that is mushrooming throughout Indonesia, because coffee shops are considered a gathering place that is in great demand today by all types of people. NAMA Coffee is one of the MSME-based coffee shops in Cimahi City that has survived from 2018 to the present. In the development of this increasingly diverse coffee shop business, of course, NAMA Coffee must have uniqueness and distinctiveness so that it is remembered and remembered by consumers, one way is to improve, or add to the quality of service to consumers by conducting interpersonal communication interactions carried out by NAMA Coffee baristas to consumers. The research used a qualitative method with a case study approach, interpersonal communication theory. The results of this study are the interpersonal communication of NAMA Coffee baristas to consumers by describing the interpersonal communication process of NAMA Coffee baristas to consumers, barriers to interpersonal communication of NAMA Coffee baristas to consumers when interacting, and the purpose of NAMA Coffee baristas implementing interpersonal communication to consumers in running a business in a coffee shop. Interpersonal communication interactions carried out by baristas can change the concept of "buyers" to "customers" because of the closeness and familiarity that occurs with consumers, so NAMA Coffee is expected to achieve and meet predetermined targets. Abstrak. Saat ini bisnis coffee shop merupakan salah satu bisnis yang tengah menjamur diseluruh penjuru Indonesia, karena coffee shop dinilai sebagai tempat berkumpul yang amat diminati pada zaman ini oleh semua jenis kalangan. NAMA Coffee merupakan salah satu coffee shop berbasis UMKM di Kota Cimahi yang masih bertahan dari 2018 hingga saat ini. Dalam perkembangan bisnis coffee shop yang semakin beragam ini, tentunya membuat NAMA Coffee harus memiliki keunikan dan kekhasan agar dikenang dan diingat oleh konsumen, salah satu caranya yaitu memperbaiki, maupun menambahkan kualitas pelayanan terhadap konsumen dengan melakukan interaksi komunikasi interpersonal yang dilakukan oleh barista NAMA Coffee kepada konsumen. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus, teori komunikasi interpersonal. Hasil dari penelitian ini adalah komunikasi interpersonal barista NAMA Coffee kepada konsumen dengan memaparkan proses komunikasi interpersonal barista NAMA Coffee kepada konsumen, hambatan komunikasi interpersonal barista NAMA Coffee kepada konsumen ketika berinteraksi, dan tujuan barista NAMA Coffee menerapkan komunikasi interpersonal kepada konsumen dalam menjalakan bisnis di coffee shop. Interaksi komunikasi interpersonal yang dilakukan barista dapat merubah konsep “pembeli” menjadi “pelanggan” karena adanya kedekatan dan keakraban yang terjadi dengan konsumen, dengan begitu NAMA Coffee diharapkan dapat mencapai dan memenuhi target yang telah ditentukan.